2021
DOI: 10.3390/nu13072339
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of the Co-Occurrence of Overweight or Obesity and Micronutrient Deficiencies among Adults in the Philippines: Results from a National Representative Survey

Abstract: The double burden of malnutrition (DBM) affects many low- and middle-income countries. However, few studies have examined DBM at the individual level, or undernutrition and overnutrition co-occurring within the same person. This study aims to investigate the prevalence and determinants of DBM among adults in the Philippines. Data from the 2013 National Nutrition Survey were used. The sample size in the analysis was 17,010 adults aged ≥20 years old, after excluding pregnant and lactating women. DBM was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
5
9
1
Order By: Relevance
“…The observed differences in dietary patterns across ethnic groups might explain this trend [38]. Additionally, the study found that married individuals were more likely to be overweight and obese compared to single people, a finding consistent with other studies [21,23,26,39]. The hypothesis is that having an obese spouse increases the likelihood of becoming obese due to comparable lifestyle behaviors [40].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed differences in dietary patterns across ethnic groups might explain this trend [38]. Additionally, the study found that married individuals were more likely to be overweight and obese compared to single people, a finding consistent with other studies [21,23,26,39]. The hypothesis is that having an obese spouse increases the likelihood of becoming obese due to comparable lifestyle behaviors [40].…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that there has been a notable increase in the prevalence of overweight among Malaysian adults. Furthermore, the prevalence of overweight in Malaysia was higher than that observed in southern China [20], and most Southeast Asian countries [21-27], except for Brunei [28], but lower than the rates reported in the United States [29]. This finding is concerning, as it indicates that a significant proportion of Malaysian adults are overweight.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding factors associated with co-occurrence of OWOB and anemia: being older age, married and richer wealth status [ 16 , 17 ], urban residency [ 16 , 18 ], being separated/divorced, widowed, unemployed, level of educational attainment [ 17 ], were significantly associated with co-occurrence of overweight/obesity and anemia. Besides, television watching [ 19 , 20 ], higher education [ 21 ], not working [ 19 ], use of hormonal contraception [ 22 , 23 ], and type of toilet facility [ 24 ], were associated with overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous occurrence of overweight/ obesity and Anemia was thought to be largely preventable, easy to treat if detected early, and approaches of control and prevention well-documented [ 17 , 18 ]. In 2012, the 65th World Health Assembly approved an action plan and global targets for maternal, infant, and child nutrition, with a target to reduce anemia prevalence by 50% and zero growth of overweight/obesity in reproductive-age women by 2025, standing from 2011 levels [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation